Extensions for probabilistic constrained programming problems: the cases of non-continuous unit commitment and bilinear energy portfolio management - Ramalho, Guilherme Matiussi (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2019.